EFFECT OF VACUM TREATMENT ON TECHNOLOGICAL PROPERTIES OF HEAT-RESISTANT CERAMZYT-CONCRETE ON COMPOSITIONAL BINDING - Sh. A. Alimuradov; A. M. Gadzhiev; Kh. N. Khadzhishalapov; T. A. Hezhev (Вестник Дагестанского государственного технического университета: Технические науки, 2019)
Objectives The aim of the study is to study the effect of vacuum treatment, heating temperature, mixing time and load force on the strength of heat-resistant expanded clay concrete for lining thermal units.Method The study is based on the vacuum processing technology of heat-resistant concrete based on a composite binder for lining the hearth of a trolley of a brick kiln, vacuum-packed concrete mix.Result The effect of vacuum processing of the mixture on the technological properties of heat-resistant expanded clay concrete on a composite binder made from Portland cement and finely ground expanded clay activated in a planetary mill (Activator-4M) is investigated. Compositions have been developed and the technological properties of expanded clay concrete have been investigated depending on the heating temperature and the amount of finely ground additives.Conclusion The results of the analysis of the dependence of the strength of expanded clay concrete on the heating temperature, the mixing time and the load strength confirm that the concrete strength indicators during evacuation are higher than for concrete without vacuum treatment; the increase in concrete strength after vacuum treatment under various technological exposure conditions is explained by an increase in workability indicators, which is characterized by the mobility and stiffness of the concrete mixture, denser packing of aggregate in the concrete structure, and also the large effect of vacuum compaction associated with the suction of water and air as well as static sealing due to the difference in atmospheric pressure and vacuum cavity pressure. The magnitude of the effective force reaches 70-75 kN / m2 with the removal of water and air from the vacuum surface; the pressure transmitted to the concrete is reduced, since part of the load is spent on determining the forces of internal friction and the development of contact stresses in the solid phase.